2023
DOI: 10.1002/jia2.26158
|View full text |Cite
|
Sign up to set email alerts
|

A trial of nurturing care among children who are HIV‐exposed and uninfected in eSwatini

Andrea Ruff,
Xolisile Dlamini,
Bareng AS Nonyane
et al.

Abstract: IntroductionChildren who are HIV‐exposed and uninfected (CHEU) are a growing population at potential risk of poor neurocognitive development. We tested a nurturing care intervention on children's neurocognitive development and maternal depressive symptoms (primary) with mediation through caregiving activities (secondary).MethodsThis study was conducted among six intervention and nine comparison antenatal‐care/prevention of vertical transmission (ANC/PVT) HIV clinics in eSwatini. We enrolled pregnant women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…A trial in Eswatini conducted by Ruff and colleagues evaluated an intervention delivered by mentor mothers using the WHO's Nurturing Care Framework to improve nurturing care in high HIV burden settings [ 31 ]. Mother‐child pairs took part in the experiment in which the standard of care was compared to the intervention [ 31 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A trial in Eswatini conducted by Ruff and colleagues evaluated an intervention delivered by mentor mothers using the WHO's Nurturing Care Framework to improve nurturing care in high HIV burden settings [ 31 ]. Mother‐child pairs took part in the experiment in which the standard of care was compared to the intervention [ 31 ].…”
mentioning
confidence: 99%
“…A trial in Eswatini conducted by Ruff and colleagues evaluated an intervention delivered by mentor mothers using the WHO's Nurturing Care Framework to improve nurturing care in high HIV burden settings [ 31 ]. Mother‐child pairs took part in the experiment in which the standard of care was compared to the intervention [ 31 ]. The authors found that a Nurturing Care Framework of activities delivered by mentor mothers can viably be integrated into antenatal care clinics and early intervention can reduce neurocognitive disparities.…”
mentioning
confidence: 99%